Chiari‐Like Malformation and Syringomyelia in American Brussels Griffon Dogs. (21st August 2014) - Freeman, A.C.; Platt, S.R.; Kent, M.; Huguet, E.; Rusbridge, C.; Holmes, S.
<x xml:space="preserve">Abstract</x> Background Although Chiari‐like malformation (CM) and syringomyelia (SM) have been described in many small breed dogs, the prevalence and clinical manifestations of this complex have not been documented in a large cohort of American Brussels Griffon (ABG) dogs. Objectives To characterize the clinical and magnetic resonance imaging (MRI) features of CM and SM in the ABG breed. Animals Eighty‐four American Kennel Club registered ABG dogs were recruited. Methods Prospective study. Complete histories and neurologic examinations were obtained before MRI. Images were blindly reviewed and calculations were made by using OsiriX. All analyses were performed by Student's t‐test, Spearman's correlation, ANOVA, and chi‐square test where appropriate. Results Chiari‐like malformation and SM were present in 65% and 52% of dogs, respectively. Twenty‐eight percent of dogs had neurologic deficits and 20% had neck pain. Mean central canal (CC) transverse height was 2.5 mm with a mean length of 3.6 cervical vertebrae. Neurologic deficits were significantly associated with a larger syrinx (P = .04, P = .08) and syrinx size increased with age (P = .027). SM was associated with a smaller craniocervical junction (CCJ) height (P = .04) and larger ventricles (P = .0001; P < .001). Conclusions and Clinical Importance Syringomyelia and CM are prevalent in American Brussels Griffon dogs. Syrinx size is associated with neurologic deficits, CM, larger ventricles, a smaller craniocervical junction height, neurologic deficits, and cerebellar herniation. Fifty‐two percent of dogs with a SM were clinically normal.